Analysis of Statement Branch and Loop Coverage in Software Testing with Genetic Algorithm - Rizal Broer Bahaweres; Khoirunnisya Zawawi; Dewi Khairani; Nashrul Hakiem (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Software testing is one important aspect of the software development process. About 50% of the time and cost in the software development process used for software testing process. There are two methods of software testing, black-box testing and white-box testing. This research using white-box testing. Software testing can be done manually or automatically. Based on research conducted, genetic algorithm has been widely implemented in software testing, such as test data generator. The purpose of this study is to apply a genetic algorithm in software testing and comparing the results with manual testing, automated, and automated with genetic algorithm. The test parameters are coverage measurements (statement, branch and loop coverage) and the time of testing. The conclusion of this study is automated testing with genetic algorithm requires fewer time and test cases to achieve coverage of 100%